Ultra Structural Characterisation of Tetherin - a Protein Capable of Preventing Viral Release from the Plasma Membrane - Gupta, Ravindra K. (Molecular Diversity Preservation International (MDPI), 2010)
Tetherin is an antiviral restriction factor made by mammalian cells to protect them from viral infection. It prevents newly formed virus particles from leaving infected cells. Its antiviral mechanism appears to be remarkably uncomplicated. In 2 studies published in PLoS Pathogens electron microscopy is used to support the hypothesis that the tethers that link HIV-1 virions to tetherin expressing cells contain tetherin and are likely to contain tetherin alone. They also show that the HIV-1 encoded tetherin antagonist that is known to cause tetherin degradation, Vpu, serves to reduce the amount of tetherin in the particles thereby allowing their release.